Characterization of redox and salinity-tolerant alkaline protease from Bacillus halotolerans strain DS5 - Wen, Yangxuan; Qiang, Jiyu; Zhou, Guixu; Zhang, Xiaobo; Wang, Lei; Shi, Yawei (Frontiers in Microbiology, 2022)
Bacillus halotolerans DS5 was isolated and identified as halophilic microbe according to 16S rRNA analysis and the physical and chemical indices of the strain. A new alkaline protease (designated as prot DS5) from Bacillus halotolerans DS5 was produced, purified, and characterized. After 12 h incubation in the medium with 1% dextrin, 0.5% NaCl, 2% soluble starch and 1% yeast extract (pH 7.0), it could reach the maximum enzyme activity (279.74U/mL). The prot DS5 was stable in the pH range of 6.0-12.0 and the temperature range of 40-60 ℃, with maximal hydrolytic activities at pH 9 and at 50 ℃. In the presence of Ca2+, Mn2+, Ba2+, Mg2+, and Fe3+, protease activity was enhanced. The prot DS5 maintained highly stable in NaCl up to 2.5mol/L, reducing and oxidizing agents. The prot DS5 also exhibited compatibility in other detergent ingredients such as nonionic and anionic surfactants. These properties of prot DS5 make this enzyme suitable for various industrial applications (e.g., detergents, leather).